A rocky mountain christmas ebook - Johnstone, William W. (2012)
USA Today bestselling author: The families Jensen and MacCallister reunite in a gripping tale of tragedy, survival, love, and maybe even a miracle . . . Three days before Christmas, Matt Jensen is traveling the Denver and Pacific railway when an avalanche slams down onto the train, trapping it in desolate Trout Creek Pass. But it wasn't an act of nature that caused the accident; it was a gang of outlaws attempting to rescue their leader, who is being taken to Red Cliff to be hanged. As Smoke Jensen and Duff MacCallister frantically try to make their way to the scene, Matt struggles to save the survivors, among them a beautiful young woman with a dark past, a merchant seaman turned rancher, and a senator with his very ill young daughter. Starving under a bitter, driving snow in the brutal, unforgiving Rocky Mountains, and surrounded by armed and desperate outlaws, Matt still dreams of making it home for Christmas. But unless fate lends a hand, nobody will. "An exciting visit to the old west of gunfights and cattle drives." — RT Book Reviews